Communism and its collapse - White, Stephen, 1945- (Routledge, 2001)
Ranging from the Russian revolution of 1917 to the collapse of Eastern Europe in the 1980s this study examines Communist rule. By focusing primarily on the USSR and Eastern Europe Stephen White covers the major topics and issues affecting these countries, including: * communism as a doctrine * the evolution of Communist rule * the challenges to Soviet authority in Hungary and Yugoslavia * the emerging economic fragility of the 1960s * the complex process of collapse in the 1980s. Any student or scholar of European history will find this an essential addition to their reading list.
Keywords: Communism -- Soviet Union -- History.; Communism -- Europe, Eastern -- History.; Soviet Union -- Politics and government -- 1985-1991.; Soviet Union -- History -- 1985-1991.; Europe, Eastern -- Politics and government -- 1989-; Europe, Eastern -- History -- 1989-; Communisme -- URSS -- Histoire.; URSS -- Politique et gouvernement -- 1985-1991.; URSS -- Histoire -- 1985-1991.; Europe de l'Est -- Politique et gouvernement -- 1989-; Europe de l'Est -- Histoire -- 1989-; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism.; Communism; Politics and government; Eastern Europe; Soviet Union; Kommunismus; Sozialismus; Zusammenbruch; Osteuropa; Sowjetunion; Communisme.; Verval (geschiedenis); Socialism, Communism & Anarchism.; Political Science.; Law, Politics & Government.; Since 1985; Samfundsvidenskab -- Økonomi.; History